1983
DOI: 10.3109/03009748309102902
|View full text |Cite
|
Sign up to set email alerts
|

Isometric Strength and Endurance in Patients with Severe Rheumatoid Arthritis or Osteoarthrosis in the Knee Joints

Abstract: Maximum isometric muscle strength on extension and flexion of the knee joints and endurance on extension has been studied in patients with rheumatoid arthritis (RA) and osteoarthrosis (OA), with such severe degeneration of the knees that arthroplasty was indicated. This material was compared with a group of healthy volunteers. The reduction in muscle strength was most pronounced in the RA group, which had 30-45% of the strength of the healthy volunteers. In the OA group the strength, similarly compared, was 55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
39
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(41 citation statements)
references
References 3 publications
1
39
0
1
Order By: Relevance
“…It is well known that patients with knee OA often show muscle weakness 1, 4, 5, 13-15, 17, 26-29) and functional loss 5,13,14,30,31) . With normal aging, there is a decrease in muscle bulk and strength 9,13,[32][33][34] . However, the weakness is not totally caused by an age-related reduction in muscle voluntary activity 4,9) , and it may also result from various other factors.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that patients with knee OA often show muscle weakness 1, 4, 5, 13-15, 17, 26-29) and functional loss 5,13,14,30,31) . With normal aging, there is a decrease in muscle bulk and strength 9,13,[32][33][34] . However, the weakness is not totally caused by an age-related reduction in muscle voluntary activity 4,9) , and it may also result from various other factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, the knee extension strength of the subjects with knee OA in this study may have been better than in some studies. 28,36 A lack of testing and reporting standards makes comparisons between studies difficult. Given the moderate severity level of our knee OA cohort, testing.…”
mentioning
confidence: 99%
“…36 Muscle strength testing has revealed that those with knee OA have a 25% to 45% loss of knee extension strength 6,15,39 and a 19% to 25% loss of knee…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…슬관절 골관절염은 종창, 통증, 관절의 운동 장애 등의 증상이 나타나며 3) , 동일한 연령대의 건강한 성인에 비하여 대퇴사두 근 근력, 고유수용성감각, 균형의 저하를 보인다 [4][5][6][7] . 슬관절 종창은 척수의 대퇴사두근 알파 운동 뉴런의 억제 메커니즘을 발생시켜 8) , 골관절염 환자의 보행 입각기 초기 50% 동안 근활 성도를 감소시키며, 슬관절 고유수용성 감각 기능을 저하 시킴 이 알려져 있으나 9) , 종창이 없는 슬관절 골관절염 환자에서 슬관절 통증이 대퇴 근력 약화, 고유수용성 감각 저하 및 균형 저하에 미치는 영향에 대해서는 다양한 의견이 있다.…”
unclassified